2024
DOI: 10.3390/jfb15020048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Glass Ionomer Cement Longevity in the Primary and Permanent Teeth—An Umbrella Review

Alessandro Panetta,
Pedro Lopes,
Tatiane Fernandes Novaes
et al.

Abstract: The aim of this umbrella review was to evaluate the longevity of glass ionomer cement (GIC) as a restorative material for primary and permanent teeth. Research in the literature was conducted in three databases (MedLine/PubMed, Web of Science, and Scopus). The inclusion criteria were: (1) to be a systematic review of clinical trials that (2) evaluated the clinical longevity of GICs as a restorative material in primary and/or permanent teeth; the exclusion criteria were: (1) not being a systematic review of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The Minamata Convention advocates for the phasing down of dental amalgam to mitigate the environmental risk of releasing mercury waste into the environment [ 70 ]. The available alternative direct restorative materials, such as GICs, have improved over time but still exhibit limited strength and questionable long-term performance [ 71 ]. The current study demonstrated that GIC added with elastomeric micelles exhibited satisfactory mechanical properties and ion-releasing actions, suggesting its potential as an alternative GIC material.…”
Section: Discussionmentioning
confidence: 99%
“…The Minamata Convention advocates for the phasing down of dental amalgam to mitigate the environmental risk of releasing mercury waste into the environment [ 70 ]. The available alternative direct restorative materials, such as GICs, have improved over time but still exhibit limited strength and questionable long-term performance [ 71 ]. The current study demonstrated that GIC added with elastomeric micelles exhibited satisfactory mechanical properties and ion-releasing actions, suggesting its potential as an alternative GIC material.…”
Section: Discussionmentioning
confidence: 99%
“…GICs are often improved to address their drawbacks by adding some reinforcing particles into the material, such as silver alloy particles, resin monomers, glass fillers, and zirconia ceramics [ 6 ]. Resin-modified GICs (RMGICs) are restorative materials with resin components and were developed to overcome the problems of conventional glass ionomers, such as moisture sensitivity and low initial mechanical strength [ 7 ]. Zirconia-added GICs are known as Zirconomer (white amalgam) [ 4 ], in which the glass component undergoes precise micronization to achieve ideal particle size and properties, and the uniform incorporation of zirconia fillers enhances the mechanical properties [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glass ionomer cement (GIC) serves as a dental restorative material in dentistry, utilized for filling and luting purposes. It comprises silicate glass powder and polyacrylic acid, forming an ionomer [ 1 ]. Its primary function is to prevent dental caries, owing to its strong adhesive bond properties with tooth structure, facilitating a tight seal between the tooth's internal structures and its surroundings.…”
Section: Introductionmentioning
confidence: 99%